Tension and bending tests in roots of two tropical species - Valdés-Rodríguez, Ofelia Andrea; Jimenez Alonso, Ángel Eduardo; Servín Martínez, Alberto; Tejero-Andrade, José (Instituto de Ecología, A.C., 2020)
Plant roots help to avoid soil loss since they form meshes that retain it, especially in sandy soils with low cohesion. However, technical documentation over the execution of tests to characterize roots is scarce; therefore, a detailed approach is required in order to perform reliable studies. The objectives of this work are to document and characterize the mechanical properties of the roots of two tropical species through tension and bending tests. To this end, special devices were designed to hold roots of Jatropha curcas L. and Ricinus communis L. extracted from sandy soils. The roots were subjected to tension and bending tests and their corresponding modulus of Young were estimated, as the maximum bending stresses. The Young tension moduli varied between 6.27 MPa to 334 MPa for Ricinus and 4.56 MPa to 271 MPa for Jatropha, with diameters between 0.5 mm and 6.8 mm for both species; during the bending tests, the roots never reached the breaking point, but they registered maximum stress values of 21 MPa and 28 MPa for Ricinus and Jatropha respectively. It is concluded that roots of Jatropha and Ricinus have low moduli of elasticity values, similar to other herbs and trees roots, with a very high flexibility, comparable to low density polyethylene.